The relationship between executive functions and fluid intelligence in Parkinson's disease. - Roca, M; Manes, F; Chade, A; Gleichgerrcht, E; Gershanik, O; Arévalo, G; Torralva, T; Duncan, J (2012)
BACKGROUND: We recently demonstrated that decline in fluid intelligence is a substantial contributor to frontal deficits. For some classical 'executive' tasks, such as the Wisconsin Card Sorting Test (WCST) and Verbal Fluency, frontal deficits were entirely explained by fluid intelligence. However, on a second set of frontal tasks, deficits remained even after statistically controlling for this factor. These tasks included tests of theory of mind and multitasking. As frontal dysfunction is the most frequent cognitive deficit observed in early Parkinson's disease (PD), the present study aimed to determine the role of fluid intelligence in such deficits. METHOD: We assessed patients with PD (n=32) and control subjects (n=22) with the aforementioned frontal tests and with a test of fluid intelligence. Group performance was compared and fluid intelligence was introduced as a covariate to determine its role in frontal deficits shown by PD patients. RESULTS: In line with our previous results, scores on the WCST and Verbal Fluency were closely linked to fluid intelligence. Significant patient-control differences were eliminated or at least substantially reduced once fluid intelligence was introduced as a covariate. However, for tasks of theory of mind and multitasking, deficits remained even after fluid intelligence was statistically controlled. CONCLUSIONS: The present results suggest that clinical assessment of neuropsychological deficits in PD should include tests of fluid intelligence, together with one or more specific tasks that allow for the assessment of residual frontal deficits associated with theory of mind and multitasking.